1999
DOI: 10.1001/archotol.125.9.953
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Esophageal Injury in Pediatric Patients After Hair Relaxer Ingestion

Abstract: In our experience, hair relaxer ingestion makes up a significant proportion of all children admitted to the hospital for caustic ingestion. No significant esophageal injury was associated with hair relaxer ingestion, suggesting that endoscopy may not be necessary in these patients. Alternative management is suggested. We believe that patients who ingest hair relaxer should be admitted to the hospital for observation if parents are thought to be unreliable, and should undergo endoscopy if they cannot tolerate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Early classification of caustic substance induced injuries may be beneficial in predicting outcomes [ 19 , 20 ]. Though there are no strict guidelines regarding when endoscopy is indicated, ingestion of larger amounts of corrosives, persistent symptoms, as well as suicidal intention are considered indications for endoscopy in the absence of a third degree burn of the hypopharynx [ 21 , 22 ]. Flexible endoscopy and concurrent endoscopic ultrasound using a high-frequency catheter probe have decreased the rate of perforation that occurs with rigid instruments [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early classification of caustic substance induced injuries may be beneficial in predicting outcomes [ 19 , 20 ]. Though there are no strict guidelines regarding when endoscopy is indicated, ingestion of larger amounts of corrosives, persistent symptoms, as well as suicidal intention are considered indications for endoscopy in the absence of a third degree burn of the hypopharynx [ 21 , 22 ]. Flexible endoscopy and concurrent endoscopic ultrasound using a high-frequency catheter probe have decreased the rate of perforation that occurs with rigid instruments [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our endoscopic findings, there were no adverse clinical sequelae observed during follow-up. When our data were combined with those from all prior published studies, we found that hair relaxer ingestion had a relatively benign clinical course (1,(10)(11)(12)16).…”
Section: Discussionmentioning
confidence: 86%
“…In our experience, ingestion of hair relaxer, an alkaline cream (pH of 11.2-11.9) applied to hair to straighten or smooth its texture, has become increasingly common. The few published studies describing the clinical or endoscopic outcome of the ingestion of hair relaxer suggest that mucosal injury is uncommon (1,5,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%